B Cell Tolerance to Deiminated Histones in BALB/c, C57BL/6, and Autoimmune-Prone Mouse Strains - Dwivedi, Nishant; Hedberg, Annica; Zheng, Ying Yi; Neeli, Indira; Satoh, Minoru; Morel, Laurence; Rekvig, Ole Petter; Radic, Marko (Frontiers in Immunology, 2017)
Deimination, a posttranslational modification of arginine to citrulline carried out by peptidylarginine deiminases, may compromise tolerance of self-antigens. Patients with connective tissue autoimmunity, particularly rheumatoid arthritis and systemic lupus erythematosus (SLE) or Felty’s syndrome, present with autoantibodies to deiminated histones, which thus form a category of anti-citrullinated protein antibodies (ACPA). In general, ACPA are a sensitive diagnostic for rheumatoid arthritis and may form in response to the release of nuclear chromatin (DNA plus deiminated histones) from granulocytes, usually referred to as neutrophil extracellular traps (NETs). The aim of this study was to examine spontaneously autoimmune mice for autoantibodies and T cell responses to deiminated histones. We compared IgG binding to deiminated and non-deiminated histones by ELISA and Western blotting in spontaneously autoimmune strains of (NZB x NZW) F1 and NZM2410 together with their derivative congenic strains, C57BL/6.Sle1 and C57BL/6.Sle1.Sle3, which display profound auto reactivity against nuclear self-antigens. The splenocyte proliferation against the two antigens was determined in the spontaneously autoimmune (NZB x NZW) F1 strain from which other autoimmune strains used in the study were derived. Immunizations with deiminated and non-deiminated histones were attempted in BALB/c mice to assess their splenocyte response. Splenocytes from BALB/c mice and from autoimmune mice at the time of conversion to autoimmunity proliferated strongly in response to deiminated histones, yet serum IgG from autoimmune (NZB x NZW) F1, NZM2410, and C57BL/6.Sle1.Sle3 mice displayed a remarkable bias against binding to deiminated histones. At the time of seroconversion, the antibodies already exhibited preference for non-deiminated histones and only non-deiminated histones were recovered from circulating immune complexes. Analysis of histone deimination showed constitutive deimination in thymic extracts from C57BL/6 and C57BL/6.Sle1.Sle2.Sle3 triply congenic mice and in spleens of autoimmune triply congenic mice. Our study demonstrates that tolerance mechanisms against deiminated histones are intact in BALB/c and C57BL/6 mice and continue to be effective in mice with overt autoimmunity to non-deiminated histones. We conclude that, in contrast to human RA and SLE patients, where we frequently observe autoantibodies against deiminated histones, autoimmune mice maintain strong tolerance mechanisms to prevent the development of autoantibodies to deiminated histones.